THE FIRST REPORT OF ASCHERSONIA PLACENTA BERK. ON MULBERRY FIELD IN THAILAND AND EFFECT OF PLANT EXTRACTS TO THE GROWTH OF THE FUNGUS - Kodsueb, Rampai; Lumyong, Saisamorn (Life Sciences and Environment Journal, 2017)
An entomopathogenic fungus, Aschersonia sp., found on mulberry leaves (Morus alba L.) was investigated during cultivation of mulberry leaves for silkwormrearing in Kamphaeng Phet province, Thailand. The silkworms had diarrhea and subsequent mortality after consumption of leaves colonized by this fungus. Microscopic and macroscopic characteristics of the fungus on substrate were examined and pure culture was isolated. Colony morphology of the pure culture obtained then has been investigated. Identification of the fungus based on morphological characteristics suggesting it is A. placenta Berk. Attempt to inhibit the growth of the fungus using plant extracts in a laboratory scale has been done. Methanol extracts of Rajabhat J. Sci. Humanit. Soc. Sci. 18(1): 188-201, 2017 . 189 Alpinia galanga (L.) Willd., Amaranthus viridis L., Tinospora crispa (L.) Miers ex Hook.f. & Thomson and Zingiber officinale Roscoe were added to the medium and tested for their ability to control fungal growth in the Petri dish. All methanol extracts, except for A. viridis, inhibited the growth of Aschersonia placenta, where methanol extracts from T. crispa showed the highest inhibition against the growth of this fungus with heat resistant properties after sterilization via autoclaving.